Political Representation of Abdullah Gathmyr in Indonesia's Liberal Democracy - Syukri, Ahmad; Anis Malik Thoha (Universitas Islam Negeri Raden Intan Lampung, 2025)
This article analyses the manifestation of Abdullah Gathmyr's political representation as a legislator of the Nahdlatul Ulama (NU) Party in South Sumatra in the context of Indonesia's liberal democracy during the period 1956-1958. It employs a qualitative approach, combining parliamentary discourse analysis with Ricoeur's hermeneutics. The main findings identify three dimensions of political representation: traditional Islamic ideology, the South Sumatra region, and the Hadhrami-Indonesian ethno-cultural community. Abdullah Gathmyr embodied a model of moderate Islamic leadership that successfully integrated the conventional values of Ahlus Sunnah wal jamaah (Aswaja) with modern democratic practices. Islamic traditionalism can play a constructive role in democratic systems through coalition building and inclusive governance. Abdullah Gathmyr's multidimensional representation model offers a blueprint for political practitioners to develop authentic yet adaptive leadership in the context of modernity. The article demonstrates that Islamic political moderation integrates religious values and modern practices without requiring secularisation. Intersectionality in political representation, which combines religious-political, regional, and ethnocultural identities, provides a theoretical framework for understanding the complexity of political representation in multicultural societies